Decay of Genes Encoding the Oomycete Flagellar Proteome in the Downy Mildew Hyaloperonospora arabidopsidis - Judelson, Howard S.; Shrivastava, Jolly; Manson, Joseph (PLOS ONE, 2012)
Zoospores are central to the life cycles of most of the eukaryotic microbes known as oomycetes, but some genera have lost the ability to form these flagellated cells. In the plant pathogen Phytophthora infestans, genes encoding 257 proteins associated with flagella were identified by comparative genomics. These included the main structural components of the axoneme and basal body, proteins involved in intraflagellar transport, regulatory proteins, enzymes for maintaining ATP levels, and others. Transcripts for over three-quarters of the genes were up-regulated during sporulation, and persisted to varying degrees in the pre-zoospore stage (sporangia) and motile zoospores. Nearly all of these genes had orthologs in other eukaryotes that form flagella or cilia, but not species that lack the organelle. Orthologs of 211 of the genes were also absent from a sister taxon to P. infestans that lost the ability to form flagella, the downy mildew Hyaloperonospora arabidopsidis. Many of the genes retained in H. arabidopsidis were also present in other non-flagellates, suggesting that they play roles both in flagella and other cellular processes. Remnants of the missing genes were often detected in the H. arabidopsidis genome. Degradation of the genes was associated with local compaction of the chromosome and a heightened propensity towards genome rearrangements, as such regions were less likely to share synteny with P. infestans.